PERAN IBU RUMAH TANGGA DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA MELALUI MITRA APLIKASI CHILIBELI DI KECAMATAN PONDOK GEDE - Sugeng Santoso (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
In their daily life, the role of IRT is always associated with roles related to affairs, kitchens, wells, and mattresses. However, nowadays, according to some sections of society, the stigma of IRT has shifted to an important role in helping the welfare of the family. This role is also increasingly important during the Covid-19 pandemic which attacks many family economic problems. In overcoming the above, many strat-ups have emerged with social objectives to help the productivity of IRTs in carrying out their roles, one of which is the Chilibeli application. Chilibeli is an online shopping application for daily products such as fruit, vegetables, basic necessities, and other household needs that carries the concept of social commerce - buying and selling activities that involve social interaction between users in a community through online and offline social networks. This study uses a descriptive approach by interviewing partners or housewives who are members of chilibeli partners. Sources of data used are direct interviews with housewives who are members of Chilibeli partners located in Pondok Gede District, Bekasi City covering the villages of Jatibening, Jatibening Baru, Jaticmpaka, Jatimakmur, Jatiwaringin The various benefits that can be felt by housewives who are members of the Chilibeli partnership include: a) getting commissions and loyalty bonuses for monthly sales. b) If the company's sales target is achieved, then as a partner can get a bonus of 0.5 grams of Precious Metals (certain categories). C) can help neighbors by providing staple products that have lower prices when compared to prices in other stores. D). Can work without leaving home and children, working flexible hours.